Semiotic analysis of commercials – A methodological discussion - Jelena Vasiljević (University of Belgrade, 2016)
Essay deals with the problem of applying semiotics in the analysis of commercials. The discussion is initiated by a concrete segment of such practice-thesis prepared under the mentorship of Daniel Chandler, a known author in the field of semiotic and the head of the Semiotics of commercials, a seminar found on the post graduate level of a welsh university. After demonstrating the methodological steps and fundamental ideas present in these papers, the validity of such an enterprise, in view of the specifics of commercials as part of a semiotic analysis, will be examined. Special attention is conferred to the problem of ideological and critical aspect that is ascertained in such an analysis, as a tension in between structurally, namely socially, orientated semiotic.